‘Within or outside Canada’: The Charter’s application to the extraterritorial activities of the Canadian Security Intelligence Service - West, Leah (University of Toronto Law Journal, 2022)
Since the swift passage of the Anti-Terrorism Act in 2015, the Canadian Security Intelligence Service (CSIS) has had the unprecedented and highly controversial authority to take ‘reasonable and proportionate’ measures to reduce threats to Canadian security. While there are some limits to the types of measures CSIS can employ, the Canadian Security Intelligence Service Act permits the use of measures that would otherwise contravene the laws of Canada or limit a right protected by the Canadian Charter of Rights and Freedoms so long as they are judicially authorized by the Federal Court. As new threats proliferate around the world, it is anticipated that CSIS will increasingly carry out this mandate overseas. Yet review bodies tasked with monitoring CSIS’s use of threat reduction measures (TRMs) report that CSIS has never sought judicial authorization to conduct a TRM. Why? One answer may be that CSIS has concluded that the Charter does not govern actions carried out abroad, and, as such, their extraterritorial conduct falls beyond the reach and oversight of the Federal Court. Whether the Charter applies to CSIS’s overseas conduct ostensibly lies in the Supreme Court of Canada’s leading case on the extraterritorial application of the Charter, R v Hape. This article canvasses domestic and international law, as well as intelligence law theory, to explain why that presumption is wrong. Wrong, not least because the majority opinion in Hape is deeply flawed in its analysis and application of international law. But also, because intelligence operations are so distinguishable from the transnational criminal investigations at issue in Hape, the Court’s findings are inapplicable in the former context. In short, this article demonstrates that applying Hape to the actions of CSIS officers not only leaves their actions beyond the scrutiny of Canadian courts but also creates a significant human rights gap.